Optimal isolation and characterisation of chondroitin sulfate from rabbit fish (Chimaera monstrosa). (15th April 2019) - Vázquez, José Antonio; Fraguas, Javier; Novoa-Carballal, Ramon; Reis, Rui L.; Pérez-Martín, Ricardo I.; Valcarcel, Jesus
Highlights: Chondroitin sulfate (CS) is isolated for the first time from Rabbit fish. The isolation process is optimized by response surface methodology. CS is obtained at two purity levels, suitable for different applications. CS shows predominant 6S-GalNAc sulfation and molecular weights of 51–55 kDa. Abstract: Chondroitin sulfate (CS) is a glycosaminoglycan widely explored for cartilage regeneration. Its bioactivity is influenced by sulfation degree and pattern, and distinct sulfation in marine CS may open new therapeutic possibilities. In this context, we studied for the first time the isolation and characterisation of CS from Rabbit Fish ( Chimaera monstrosa ). We propose an efficient process starting with enzymatic hydrolysis, followed by chemical treatments and ending in membrane purification. All steps were optimised by response surface methodology. Chemical treatment by alkaline-hydroalcoholic precipitation led to 99% purity CS suitable for biomedical and pharmaceutical applications, and treatment by alkaline hydrolysis yielded CS adequate for nutraceutical formulations (89% purity). Molecular weight and sulfation profiles were similar for both materials. Gel permeation chromatography analyses resulted in molecular weights (Mn) of 51–55 kDa. NMR and SAX-HPLC revealed dominant 6S-GalNAc sulfation (4S/6S ratio of 0.4), 17% of GlcA 2S-GalNAc 6S and minor quantities of other disaccharides.